USING COUPLES' DISCORDANT REPORTS TO ESTIMATE FEMALE COVERT USE OF MODERN CONTRACEPTION IN SUB-SAHARAN AFRICA. Issue 3 (19th July 2017) - Gasca, Natalie C.; Becker, Stan
Summary: Substantial numbers of married women use contraceptives without their partner's knowledge in sub-Saharan Africa, but studies of female covert use across time are rare. This study investigates the levels, trends and correlates of covert use in nine countries and determines which contraceptive methods are more frequently used covertly by women. Data from monogamous couples in Demographic and Health Surveys were used from nine sub-Saharan African countries that had experienced an increase of 10 percentage points in current modern contraceptive use between an earlier (1991–2004) and later (2007–2011) survey. Covert use was indirectly estimated as the percentage of women who reported a female modern method whose husband did not report a modern method. The percentage of women using covertly increased in eight of the countries studied (significantly in three of them), yet when comparing across countries cross-sectionally, covert use was lower where contraceptive prevalence was higher. In general, women with more years of schooling and those with larger spousal schooling gaps had lower odds of covert use. There was no significant difference between covert and open injectable use, though more than half of both groups used this method in the later surveys. Encouraging couple communication about contraception, where the woman feels it is safe to do so, could be an important strategy to minimize covert use. Further research is needed to better identify the contraceptive prevalence and social context in which covert use declines within a country.